Current status of biomarker research in neurology - Polivka, Jiri; Polivka, Jiri; Krakorova, Kristyna; Peterka, Marek; Topolcan, Ondrej (The EPMA journal, 2016)
Neurology is one of the typical disciplines where personalized medicine has been recently becoming an important part of clinical practice. In this article, the brief overview and a number of examples of the use of biomarkers and personalized medicine in neurology are described. The various issues in neurology are described in relation to the personalized medicine and diagnostic, prognostic as well as predictive blood and cerebrospinal fluid biomarkers. Such neurological domains discussed in this work are neuro-oncology and primary brain tumors glioblastoma and oligodendroglioma, cerebrovascular diseases focusing on stroke, neurodegenerative disorders especially Alzheimer's and Parkinson's diseases and demyelinating diseases such as multiple sclerosis. Actual state of the art and future perspectives in diagnostics and personalized treatment in diverse domains of neurology are given.
Keywords: Biomarker; Parkinson’s disease; Multiple sclerosis; Alzheimer’s disease; Predictive preventive personalized medicine; Stroke; Neuro-oncology; Personalized medicine